The influence of social media food content on the Greek travel destination image - Koutoulaki, Evanthia (2022)
In the modern days, tourists tend to increasingly use social media during the pre-trip, on-site (in-situ) experiences, and feedback levels. These are progressively influencing travellers’ behaviours, as well as forming the experiences, impressions and ideas of consumers. This thesis intends to explain how food-related content on social media can influence the destination image of Greece, considering the value of food as a unique and distinguishing element of the touristic destinations and identifying the power of social media food content on developing gastronomic tourism and improving the destination image of Greece. We aim to recognize the power of social media channels and particularly Instagram, in impacting destination choice, offering inspiration for travel planning as well as interpreting the relationship between Greek gastronomy and travelling in the digital era. To achieve our goals, both primary and secondary data were collected. The literature review is performed from the broadest to the most exact relevant subjects. The data collection, as well as analysis, have been implemented through the qualitative method. To clarify the questions asked and to attain the scope of this thesis, we resort to the focus group technique, collecting ideas from several young culinary tourists belonging to the target group of Millennials and Generation Z. The combination of both primary and secondary data offered significant findings that contributed to recognising the value of social media food content on the destination image of Greece. It is worth mentioning that the results of this research prompted that there is a strong impact of social media food content on consumer behaviours, travel choices, as well on the motivations of young gastronomic tourists.